Exploration of Students’ Strategic Competence in Higher-Order Thinking Skills Based Linear Programming Topic in terms of Mathematics Learning Styles - Sabri Sabri; Suradi Suradi; Abdilla Nurul Azisah M.N. (PT Mattawang Mediatama Solution, 2023)
This study is descriptive-explorative in nature employing a mixed-method approach and aiming to know students’ strategic competence in HOTS-based linear programming topic in terms of mathematics learning styles. There were 6 subjects in grade XI in Polewali Mandar that represent each learning style-strategic competence category. The instruments were questionnaire, test, and interview guidance. The questionnaire and test scores were analyzed quantitatively whereas test answers and interview results were analyzed qualitatively. The results show that of the 58 students who answered the test, they had low strategic competence in average also lack ability in each component. Visual learners are unable to formulate problem, incorrect in representing problem and unable to solve it correctly, tend to misinterpret verbal information and to involve visual presentations. An auditory learner formulated problem, however, the auditory learners are not completely correct in representing problem and unable to solve it correctly, tend to narrate the strategy, and are the best in interpreting verbal information. Meanwhile, kinesthetic learners are unable to formulate problem, not completely correct in representing problem and unable to solve it correctly, are the best in problem representation approach, but tend to be rigid in doing the strategy.